THE ROLE OF EMOTION-BASED LEARNING IN ENHANCING ENGLISH LANGUAGE PROFICIENCY IN HIGHER EDUCATION INSTITUTIONS OF UZBEKISTAN - Ibraximova Maftuna Safarali qizi (The latest pedagogical and psychological innovations in education, 2025)
This article examines the role of emotion-based learning in developing English language proficiency among students of higher education institutions in Uzbekistan. Based on modern educational psychology, affective factors, socio-cultural context, and communicative methods, the paper argues that emotional engagement significantly enhances motivation, retention, creativity, and communicative performance. The study analyzes how emotions influence cognitive processes, explores practical tools for integrating emotional learning into English classrooms, and highlights challenges faced in Uzbek higher education. Recommendations are provided for educators to create emotionally supportive and stimulating environments that align with national language policy and current reforms in the education system.